Prototipe Sistem Informasi Retailer Industri Kreatif Di Kota Solo - Eko - Purwanto; Nurchim Nurchim; Feri Setiyono (Universitas PGRI Semarang, 2018)
Solo is a cultural city. in addition solo has some business actors in the arts and cultural arts until now still exist in production. The problems faced by UKM craft art and culture here is the lack of marketing media, therefore making the difficulty of handicraft products known by the public. Marketing media utilized include brochures, pamphlets and more. In this study the authors provide solutions by designing and making a craft sales application that is devoted to the sale of cultural arts and crafts are expected to solve existing problems.This research uses prototype method in system development. The design of the system in this study using UML system design tool (Unified Modeling Language). With use case, diagram, flowchart.The results of this study obtained from the questionnaire to the respondents consisting of respondents sellers and respondents buyers who showed results that web-based creative industry retailer applications obtained Percentage of respondents sellers Interpretation of 92% and respondents buyers interpretation of 87%. So the average of questionnaire results from both respondents is 89.5% which shows the application of creative industry retailers can be useful to help the system of art and culture arts sales in the city of Solo.